Regulation of Biobanks in France. Issue 4 (2015) - Rial-Sebbag, Emmanuelle; Pigeon, Anna
Abstract : France, a country with nearly 66 million inhabitants, contributed greatly to the construction of the European Union (EU) as one of the founder states. In 1957, the treaties establishing the European Economic Community (EEC) and the European Atomic Energy Community (Euratom) were signed by Belgium, France, Germany, Italy, Luxembourg, and the Netherlands in Rome. Today, they are referred to as the "Treaties of Rome." The French contribution to the EU has strongly influenced the political views on the development of Europe, notably pushing for a large contribution of member states to the decision making processes and to the orientation of the EU policies.